2013
DOI: 10.1371/journal.pone.0067162
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Psychotherapy with Disability Benefit Claim Closure among Patients Disabled Due to Depression

Abstract: BackgroundDepression is the most frequent reason for receiving disability benefits in North America, and treatment with psychotherapy is often funded by private insurers. No studies have explored the association between the provision of psychotherapy for depression and time to claim closure.MethodsUsing administrative data from a Canadian disability insurer, we evaluated the association between the provision of psychotherapy and short-term disability (STD) and long-term disability (LTD) claim closure by perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
2
21
2
Order By: Relevance
“…We previously found that residing in Quebec (v. Ontario) was associated with longer short-term disability claim duration, but shorter long-term disability claim duration. 4 Now, we report a similar association among SSQ claimants with psychological disorders who resided in Quebec compared with those residing elsewhere in Canada. Among claimants with musculoskeletal complaints and other illnesses, however, Quebec residency was associated with shorter short-term and longterm disability benefit duration.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…We previously found that residing in Quebec (v. Ontario) was associated with longer short-term disability claim duration, but shorter long-term disability claim duration. 4 Now, we report a similar association among SSQ claimants with psychological disorders who resided in Quebec compared with those residing elsewhere in Canada. Among claimants with musculoskeletal complaints and other illnesses, however, Quebec residency was associated with shorter short-term and longterm disability benefit duration.…”
Section: Discussionsupporting
confidence: 59%
“…Our findings are consistent with our previous study, which suggested older age, female sex (short-term disability claims only), higher salary and comorbidity were associated with longer claim duration among claimants with depression. 4 In our previous study, prolonged time to claim approval was only associated with longer long-term claim duration; in the current study, however, longer claim approval was associated with longer duration of both short-and long-term disability claims. Minimizing time to claim approval may be a promising target for reducing claim duration.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations